Streptomyces spp. From Ethiopia Producing Antimicrobial Compounds: Characterization via Bioassays, Genome Analyses, and Mass Spectrometry - Kibret, Moges; Guerrero-Garzón, Jaime F.; Urban, Ernst; Zehl, Martin; Wronski, Valerie-Katharina; Rückert, Christian; Busche, Tobias; Kalinowski, Jörn; Rollinger, Judith M.; Abate, Dawit; Zotchev, Sergey B. (Frontiers in Microbiology, 2018)
A total of 416 actinomycete cultures were isolated from various unique environments in Ethiopia and tested for bioactivity. Six isolates with pronounced anti-microbial activity were chosen for taxonomic identification and further investigation. Morphological and cultural properties of the isolates were found to be consistent with those of the genus Streptomyces, which was further confirmed by phylogenetic analysis based on 16S rRNA gene sequences. One of the isolates, designated Streptomyces sp. Go-475, which displayed potent activity against both pathogenic yeasts and Gram-positive bacteria, was chosen for further investigation. Metabolite profiles and bioactivity of Go-475 incubated on wheat bran-based solid and soya flour-based liquid media were compared using high-resolution LC-MS. This allowed identification of several known compounds, and suggested the ability of Go-475 to produce new secondary metabolites. Major anti-bacterial compounds were purified from liquid cultures of Go-475, and their structures elucidated by NMR and HRMS as 8-O-methyltetrangomycin and 8-O-methyltetrangulol. In addition, many potentially novel metabolites were detected, the majority of which were produced in solid media-based fermentation. Complete genome sequence of Streptomyces sp. Go-475 was obtained and analyzed, further confirming its great potential for production of chemically diverse secondary metabolites.